MOLYBDENUM AND TUNGSTEN IN VOLCANIC ROCKS AND IN SURFACE AND <100 °C GROUND WATERS IN ICELAND - Arnórsson S.; Óskarsson N. (My University, 2007)
The concentrations of Mo and W in tholeiite series basaltic to silicic volcanics in Iceland increase with the concentrations of incompatible magmatic elements. In normal Mid Ocean Ridge Basalt (MORB), Mo and W levels are as low as 0.03 and 0.01 ppm but in rhyolites they are up to 4 and 1.3 ppm, respectively. In the slightly evolved Tertiary tholeiites of the main study area of Skagafjördur, northern Iceland, Mo and W concentrations are 1.01 and 0.32 ppm, respectively, on average. Surface waters in this area typically contain <0.5 ppb Mo and <0.1 ppb W. Concentrations are higher in ground waters and, on the whole, they increase with increasing temperature and increasing age of these waters, being as high as ~100 ppb for Mo and ~10 ppb for W in the hottest (~90 °C) and oldest (>10,000 years) waters. In river and ground waters, the average Mo/W ratio is the same as that of the basalt host rock. On the other hand, in peat soil waters, the average Mo/W ratio is higher due to adsorption processes involving W. In river and ground waters, both Mo and W display conservative behavior. Progressive water-rock interaction leads to successively lower aquatic B/Mo and B/W ratios. However, the B/Mo and B/W ratios of the most reacted waters are considerably higher than those of the basalt due to non-stoichiometric rock dissolution: B is dissolved preferentially to both Mo and W because B is largely present in a soluble form, but Mo and W are concentrated in the Fe-Ti-oxides. These minerals are stable, under both surface and sub-surface conditions, i.e. the waters are over-saturated with respect to these minerals. The main supply of Mo and W to surface waters is from dissolution of plagioclase and pyroxene, as well as volcanic glass. Olivine is not an important source due to its scarcity in the basalts. In <30 °C ground waters, the dominant supply of Mo and W is plagioclase. At higher temperatures pyroxene also contributes, with its contribution increasing with increasing temperature, as deduced from its decreasing stability at higher temperature. Dissolution of basaltic glass produces lower B/Mo and B/W aqueous ratios than dissolution of crystalline basalt. © 2006 Elsevier Inc. All rights reserved.